Neuronal plasticity in a case with total hemispheric lesion - (:unkn) unknown (My University, 2011)
RATIONALE: The adult brain maintains the ability for reorganization or plasticity throughout life. Non-invasive techniques such as functional magnetic resonance imaging (f-MRI), Transcranial Magnetic Stimulation (TMS) and magnetoencephalography could be used to show recovery of function after stroke. OBJECTIVE: Explanation of neuronal plastisity and intra-hemisferic reorganization with functional recovery of a case who has total extensive damage on the left hemisphere. case report: Twenty-five years old female patient was admitted to our hospital with a right-sided sequel hemiparesis and homonymous hemianopia. She had right-sided paresia after an inguinal hernia operation when she was one and a half years old. On neurological examination she was speaking fluently, and cooperated on complicated comments. Motor examination revealed right-sided spastic hemiparesis predominant on distal parts and right sided visual field defect. But she was continuing her activity of daily livings without help. Her detailed neuropsycological examination revealed mild cognitive dysfunction. Cranial MRI showed total left hemisphere encephalomalasia. Right hemisphere function was noticed on task-related brain activation during voluntary movement of her right leg (she was not capable of performing right hand function tasks by herself ) on functional MRI. CONCLUSION: Cerebral lesions in the early life can be compensated with the unaffected hemisphere by the neuronal reorganisation and a patient with complete left hemisphere lesion such as our patient can speak, maintain her life without assistance but with mild cognitive decline, compared with elderly stroke patients.
Keywords: Adult; Female; Humans; Tomography, X-Ray Computed; Magnetic Resonance Imaging; Neuronal Plasticity; Cerebrum; functional MRI; hemispheric lesion; Neuronal plasticity; reorganization; Visual Fields